The Potential Proallergenic Activity of Tranzschelia pruni-spinosae and Phragmidium rubi-idaei in vitro Studies - Sztandera-Tymoczek M; Wdowiak-Wróbel S; Świderska U; Palusińska-Szysz M; Szuster-Ciesielska A (Journal of Inflammation Research)
Monika Sztandera-Tymoczek,1 Sylwia Wdowiak-Wróbel,2 Urszula Świderska,3 Marta Palusińska-Szysz,2 Agnieszka Szuster-Ciesielska1 1Department of Virology and Immunology, Institute of Biological Sciences, Maria Curie-Skłodowska University, Lublin, Poland; 2Department of Genetics and Microbiology, Institute of Biological Sciences, Maria Curie-Skłodowska University, Lublin, Poland; 3Department of Botany, Mycology and Ecology, Institute of Biological Sciences, Maria Curie-Skłodowska University, Lublin, PolandCorrespondence: Agnieszka Szuster-Ciesielska, Department of Virology and Immunology, Institute of Biological Sciences, Maria Curie-Skłodowska University, Akademicka 19, Lublin, 20-033, Poland, Tel +48 81 537 59 43, Email agnieszka.szuster-ciesielska@mail.umcs.plPurpose: Allergic diseases have escalated to epidemic levels worldwide, impacting nearly 30% of the global population. Fungi are a significant source of allergens responsible for up to 6% of respiratory diseases in the general population. However, the specific cause of respiratory allergies often remains unidentified. This study aimed to investigate the potential of two common rust fungi, Tranzschelia pruni-spinosae and Phragmidium rubi-idaei, to trigger a proinflammatory response in vitro models representing the upper and lower respiratory tract.Materials and Methods: The BEAS-2B and A549 cell lines simulated upper and lower respiratory endothelial cells. The cytotoxicity of fungal extracts was evaluated using MTT and flow cytometry assays. Cell reactive oxygen species (ROS) production was measured via flow cytometry, while ELISA tests quantified the production of proinflammatory cytokines. Immunofluorescence techniques were employed to assess cell integrity markers.Results: Extracts from T. pruni-spinosae and P. rubi-idaei significantly stimulated the production of proinflammatory cytokines IL-1β and GM-CSF in both cell lines, all of which are associated with the development of allergic responses. The increase in these cytokines and the elevated ROS production were linked to the disruption of epithelial cell junctions.Conclusion: The findings suggest the potential of T. pruni-spinosae and P. rubi-idaei extracts to collectively disrupt the epithelial barrier in the upper and lower respiratory tract by inducing proinflammatory cytokines and the production of reactive oxygen species and metalloproteinases. Although none of the above parameters was spectacularly high, all of them together could cause a decrease in the presence of tight junction proteins, such as E-cadherin and occludin, in epithelial cells.Plain Language Summary: Phytopathogenic microfungi, commonly found in human surroundings, act as plant parasites. They adversely affect crop yields, lower the quality of agricultural products, and diminish the aesthetic value of ornamental plants. Furthermore, these fungi pose a potential health risk to humans, as they are major sources of allergens. The most notable allergenic fungi include Alternaria, Aspergillus, Cladosporium, Penicillium, and Fusarium. However, even widely distributed fungi like T. pruni-spinosae and P. rubi-idaei, which infect plums and raspberries, can trigger allergic reactions. These fungi heavily infest plants, releasing vast amounts of spores, particularly in the spring, summer, and fall. This increases the risk of human exposure to allergens as the plants and their parasitic fungi spread. Since standard skin or blood tests do not always pinpoint the root causes of allergies, identifying new fungal allergens is critical for more precise hypersensitivity diagnoses. Our research indicates that parasitic microfungi exhibit pro-inflammatory solid properties, which is the basis of allergenic reactions in in vitro upper and lower respiratory tract models.Keywords: phytopathogenic microfungi, Tranzschelia pruni-spinosae, Phragmidium rubi-idaei, airway epithelial cells, inflammatory response